1984
DOI: 10.1002/jcc.540050507
|View full text |Cite
|
Sign up to set email alerts
|

Examination of formamide, formamidic acid, amidine dimers, and the double proton transfer transition states involving these dimers

Abstract: Structures and relative energies were obtained for the hydrogen bonded dimers of formamide and formamidic acid using the 3-21G basis set. A double proton transfer transition state is claimed to link these two dimers. While the structure of the transition state was intermediate between those of the two dimers, the energy was only 7.6 kJ/mol greater than the less stable formamidic acid dimer. The activation energy from the formamide dimer side of the reaction was found to be 125 kJ/mol of dimer. A similar transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…[22][23][24][25][26][27][28][29] In addition, both molecules possess an amide functional group, which is the basic building block of proteins and enzymes, and they can also be considered as models for nucleic bases. [22][23][24][25][26][27][28][29] In addition, both molecules possess an amide functional group, which is the basic building block of proteins and enzymes, and they can also be considered as models for nucleic bases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29] In addition, both molecules possess an amide functional group, which is the basic building block of proteins and enzymes, and they can also be considered as models for nucleic bases. [22][23][24][25][26][27][28][29] In addition, both molecules possess an amide functional group, which is the basic building block of proteins and enzymes, and they can also be considered as models for nucleic bases.…”
Section: Introductionmentioning
confidence: 99%
“…As an example of its application, it will be used to investigate proton transfer in two model systems: formamide and 2-pyridone (as represented in Scheme 1), because proton transfer is an ubiquitous fundamental process, particularly in biological systems. [22][23][24][25][26][27][28][29] In addition, both molecules possess an amide functional group, which is the basic building block of proteins and enzymes, and they can also be considered as models for nucleic bases. Furthermore, a comparison between formamide and 2-pyridone might disclose information on the effect of aromatic delocalization.…”
Section: Introductionmentioning
confidence: 99%
“…The true saddlepoint found at 3-21G level lies just 0.04 kcal mol-1 lower in energy (a small but significant energy difference) than the DZh structure reported previously as a transition state . 3 The corresponding energy difference at the 6-31G* level is much greater (4.2 kcal mol-1). As we see it, the high energy of the ion-pair like intermediate (compared to D) calculated with the 6-31G* basis set must to a large extent be due to separation of charges.…”
mentioning
confidence: 97%
“…Previous studies of the potential energy surfaces for such reactions within dimers have shown a concerted transfer with a highly symmetrical transition state in which the protons are located midway between the monomeric subunits.l.2 In another theoretical investigation at the Hartree-Fock (HF) level of theory (using 3-21G basis set) the formamidine dimer and its two-proton transfer reaction have been studied using the assumption that the reaction path has C2, symmetry. 3 The optimized structure of the highest energy within this restriction (a D2, structure) was assigned as the transition state for the transfer reaction.3…”
mentioning
confidence: 99%
“…(Only the planar phenyl substituent in 8 is twisted by 37.64° with respect to the amidine plane.) The analytical gradient optimization procedure of M urtagh and Sargent [9] implemented in Pople's GAU SSIAN 82 program [10], and the split-valence 3-21 G basis set [11] have been used in an IBM MVS/XA version on a C OM PAREX 7/88 com puter [12], The 3-21G basis set was selected for reasons o f economy and to aid com parison with the elaborate calculations o f Zielinski et al [13][14][15] and from our group [16,17].…”
Section: Methods Of Calculationsmentioning
confidence: 99%